Predicting Proactive Safety Behaviour of the young Malaysian workers: An ethno- methodological analysis - Rusyda (International Journal of Psychosocial Rehabilitation, 2020)
The safety behavior literature makes a distinction between compliance and proactive safety behavior (PSB), with the latter seen as being increasingly important for achieving safety outcomes in contemporary work environments. However, a review of the literature on proactive safety behavior reveals some significant gaps in our current understanding of the concept. From a theoretical perspective, there is a disconnect between how proactive behavior has been conceptualized in the recent mainstream literature on proactivity and the extant literature on proactive safety behavior. Specifically, recent theoretical developments relating to the nature, causes, and consequences of proactive behavior have not yet been incorporated into theorizing concerning proactive safety behavior. From a methodological perspective, operationalizations of proactive safety behavior have all made use of the measure of safety citizenship, and role behavior developed to measure. The measure which assesses extra role safety citizenship behavior does not appear to map well onto current definitions of what it means to be proactive in organizational settings. Furthermore, limited studies carried out to date have examined individual or organizational outcomes of proactive safety behavior, instead choosing to examine proactive safety behavioras an outcome in its own right. In this paper, we outline a new conceptual framework, which describes proactive safety behavior as a form of goal-directed self- regulatory behavior, fuelled by aspects of individual ability, motivational and opportunity. Interviews with 33 young Malaysian workers were analyzed using Leximancer to explore whether or not the theoretical framework was useful in this context. The findings were consistent with the original framework. However, analyses using Leximancer also suggested some modifications to the original framework. It helped us to gain a deeper understanding of self- regulated proactive safety behavior.